2021
DOI: 10.3390/pr9020353
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Astragaloside-Containing Polyurethane Nerve Conduits Influenced Schwann Cell Inflammation and Regeneration

Abstract: The peripheral nervous system is the bridge of communication between the central nervous system and other body systems. Autologous nerve grafting is the mainstream method for repair of nerve lesions greater than 20 mm. However, there are several disadvantages and limitations of autologous nerve grafting, thus prompting the need for fabrication of nerve conduits for clinical use. In this study, we successfully fabricated astragaloside (Ast)-containing polyurethane (PU) nerve guidance conduits via digital light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…A previous study found that the combined use of atorvastatin and AS-IV could more effectively reduce the inflammatory response in mice than either of the two agents [ 136 ]. AS-IV and polyurethane concurrently increase the levels of neuronal regeneration indicators and promote Schwann cell proliferation in mice [ 137 ]. Therefore, combination therapy with AS-IV may prevent and treat diabetes and its associated complications.…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…A previous study found that the combined use of atorvastatin and AS-IV could more effectively reduce the inflammatory response in mice than either of the two agents [ 136 ]. AS-IV and polyurethane concurrently increase the levels of neuronal regeneration indicators and promote Schwann cell proliferation in mice [ 137 ]. Therefore, combination therapy with AS-IV may prevent and treat diabetes and its associated complications.…”
Section: Discussion and Future Outlookmentioning
confidence: 99%
“…Chen et al using a digital light processing technique, fabricated astragaloside-containing polyurethane (Ast/PU) hollow conduits with dimensions 2 mm in diameter and 14 mm in length. When cultured with RSC 96 cells, the constructs showed good adhesion with flat, elongated spindle-shaped morphology on day 1 itself and gradually increased for up to 7 d [54]. In another study by Zhang et al porous waterborne polyurethane (WPU) hydrogels prepared using a freeze-drying method were seeded with PC-12 cells and cultured for 6 d to study PC-12 cell attachment and growth.…”
Section: Cell Adhesion Viability and Proliferationmentioning
confidence: 99%
“…This is because the combined use of both agents can more strongly modulate the activity of intracellular regulatory factors of T cells to ameliorate neuroinflammation [ 174 ]. Using astragaloside IV and polyurethane concurrently also dramatically increases the levels of neuronal regeneration indicators and promotes the proliferation of Schwann cells in mice [ 175 ]. Along with the observation that the combined use of atorvastatin and astragaloside IV can more effectively reduce the inflammatory response in mice than either of the two agents does [ 176 ], integrating astragaloside IV into the regimen of chemical drugs is a possible strategy to enhance the therapeutic efficiency when treatment is developed to tackle neuronal aging.…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%